Chandra Observations of Jupiter's X‐ray Auroral Emission During Juno Apojove 2017. Issue 4 (26th March 2020) - Weigt, D. M.; Jackman, C. M.; Dunn, W. R.; Gladstone, G. R.; Vogt, M. F.; Wibisono, A. D.; Branduardi‐Raymont, G.; Altamirano, D.; Allegrini, F.; Ebert, R. W.; Valek, P. W.; Thomsen, M. F.; et al.
Abstract: Jupiter's auroral X‐rays have been observed for 40 years with an unknown driver producing quasiperiodic emission, concentrated into auroral hot spots. In this study we analyze an ∼ 10‐hr Chandra observation from 18:56 on 18 June 2017. We use a new Python pipeline to analyze the auroral morphology, perform timing analysis by incorporating Rayleigh testing, and use in situ Juno observations to infer the magnetosphere that was compressed during the Chandra interval. During this time Juno was near its apojove position of ∼ 112 R J, on the dawn flank of the magnetosphere near the nominal magnetopause position. We present new dynamical polar plots showing an extended X‐ray hot spot in the northern auroral region traversing across the Jovian disk. From this morphology, we propose setting a numerical threshold of > 7 photons per 5° System III longitude × 5° latitude to define a photon concentration of the northern hot spot region. Our timing analysis finds two significant quasiperiodic oscillations (QPOs) of ∼ 37 and ∼ 26 min within the extended northern hot spot. No statistically significant QPOs were found in the southern X‐ray auroral emission. The Rayleigh test is combined with Monte Carlo simulation to find the statistical significance of any QPOs found. We use a flux equivalence mapping model to trace the possible origin of the QPOs, and thus the driver, to the dayside magnetopause boundary. Key Points: Analysis is performed on a Chandra campaign observing Jupiter's X‐ray emissions during the apojove portion of Juno's orbit on 18 June 2017 We use Juno magnetopause crossings to infer a compressed magnetosphere during the X‐ray campaign Quasiperiodic pulsing of the northern X-ray hot spot are mapped to a location close to the dayside magnetopause